ANALISIS PENGARUH LEBAR CELAH UDARA PADA CHANNEL OUTLET TERHADAP KONDISI RUANGAN DAN DAYA LISTRIK DENGAN MEMANFAATKAN PANEL SURYA - Antan Noraidi Maulana; Achmad Kusairi Samlawi; Muhammad Rijali (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2018)
Only a Part of the energy of sunlight is absorbed by solar panels during the day will be converted into electrical energy, the rest will be converted into thermal energy that conducted to the solar panel surface with high surface temperatures. High temperatures on the surface of solar panels can be combined as a trombe wall to produce a temperature gradient in the channel outlets or vents. The produced gradient temperature will create air flow velocity in the chamber and will increase due to the difference in density gradient. So heat in the room will be pushed out. This study will vary, the air gap width 3 cm, 4.5 cm and 6 cm by comparing the indoor temperature, humidity and electric power by using solar panels and without 450 tilted solar panel facing north. Room dimensions are 0.5x0.5x0.5 m, with solar panels 150x180x18 mm dimensions. Collecting data every 10 minutes from 07:00 until 19:00. The sensor used is LM35, DHT11, Voltage Sensor, and ACS712. Air condition obtained will be compared with the standard of comfort of air in the tropical building. Results obtained from the research is a widening gap Outlet Channel or ventilation in the room conditions will increase the temperature, the humidity, increase power and decrease the comfort in the room. Otherwise the narrow width of the gap or ventilation Outlet Channel it will lower the temperature, increase humidity, lower power and increased comfort in the room.